Uprość wyrażenia algebraiczne:
-7 + 3y + 2y
x - 3x + 2 - 2x - 7
-5x + 4y - y - 7x - 9y
4x + 5 - x - 4 + x - 3x
0,5a - 2a + 9 - 0,5a - 11,5
-14k + 9k - 13 + k + 3 +4k
-3k + 2m + 5m - 7 + k - m
2x - 4 + 3x - 2
x- 3y - 2x + 6y
2y - 5 - 3y - 4 - 8y + 9

3

Odpowiedzi

2010-04-13T19:51:47+02:00
-7+5y
-4x-5
-12x-6y
x+1
-2a-2,5
-10
-2k+6m-7
5x-6
-x+3y
-9y
11 4 11
2010-04-13T19:52:46+02:00
-7 + 3y + 2y = -7 + 5y
x - 3x + 2 - 2x - 7 = -4x-5
-5x + 4y - y - 7x - 9y = -12x -6y
4x + 5 - x - 4 + x - 3x = x +1
0,5a - 2a + 9 - 0,5a - 11,5 = -2a -2,5
-14k + 9k - 13 + k + 3 +4k = -10
-3k + 2m + 5m - 7 + k - m = -2k + 6m - 7
2x - 4 + 3x - 2 = 5x - 6
x- 3y - 2x + 6y = -x + 3y
2y - 5 - 3y - 4 - 8y + 9 = -9y
1 2 1
2010-04-13T19:53:03+02:00
-7+5y
-4x-5
-12x-6y
x+1
-2a-3,5
10
-2k+6m
5x-2
-1x+3y
-9y
1 1 1